Usage of Distance and Blended Learning in Educating School Librarians - Banek Zorica, Mihaela; Špiranec, Sonja; Lazić, Nikolaj (2007)
Paper shows the case study of transforming traditional learning environment (based on teacher-centred instruction), to the blended learning environment (based on student-centred instruction) using Open Source Learning Management Systems, like Moodle. Special attention was on the advantages in usage of this tool in educating LIS professionals. Authors try to investigate whether new technologies help and motivate students master the necessary knowledge, especially when applied to the mandatory courses. Differences in motivation and access to the studies between the full-time and part-time students are also compared. Data fo the evaluation have been gathered through numerous satisfaction surveys and interviews with the students of Department of Information Sciences, Faculty of Humanities and Social Sciences, University of Zagreb, both full-time and part-time, as well as through the analysis of the data from the faculty’ s e-learning system.
Projekt MZOS
ENG